Risk analysis of air quality for parameters NO2, SO2, NH3, and Ox from the area around fertilizer industries in Indonesia - Alighiri, Dante; Widodo, Naufaldi Bani; Abdullah, Ravely Adhitya; Firnanda, Indah Putri; Drastisianti, Apriliana (Journal of Natural Sciences and Mathematics Research, 2025)
Industrial zones with intensive human activities often experience air-quality degradation, particularly in areas surrounding fertilizer production facilities. This study analyzes the concentrations of nitrogen dioxide (NO₂), sulfur dioxide (SO₂), ammonia (NH₃), and oxidants (Ox) in the ambient air around fertilizer industries in Indonesia and evaluates their potential non-carcinogenic health risks. Air sampling was conducted using an InScienPro US-1012 impinger equipped with selective absorbent solutions. Pollutant concentrations were quantified using UV-Vis spectrophotometry based on the Griess–Saltzman method for NO₂, the pararosaniline method for SO₂, the indophenol method for NH₃, and the neutral buffer potassium iodide method for Ox. Concentrations were compared with national ambient air-quality standards. To strengthen the assessment, a quantitative health-risk evaluation was incorporated using the Hazard Quotient (HQ) and Hazard Index (HI), allowing for the interpretation of long-term exposure impacts. Results show that most pollutant concentrations were below regulatory limits; however, SO₂ levels at one sampling point and NH₃ levels near the production zone were elevated. The HQ–HI analysis revealed that SO₂ at the office-area sampling point (HQ = 0.794) and NH₃ inside the processing plant (HQ = 2.238) were the dominant contributors to cumulative exposure, with HI values exceeding 1 at both locations. These findings indicate potential non-carcinogenic risks for individuals chronically exposed in areas closest to emission sources. Overall, this study highlights the importance of continuous monitoring and risk-based evaluation to identify localised hotspots, inform mitigation strategies, and enhance emission control practices in fertiliser-industrial environments.